EXPRESSION OF EXTRAPOLATIVE FACTORS OF MEDICAL IMPORTANCE AND THEIR POTENTIAL ROLE IN THE DEVELOPMENT OF LEUKEMIA - Arif Malik; Muhammad Shahzad Farooq; Qasim Mehmood Janjua et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: Leukemia deﬁned as the cancer of bone marrow i.e. leading to wild proliferation of blood forming cells. The WBCs are granulocytes, which avert bacterial infection and T and B lymphocytes. Prognostic measures for the disease are still not clear whereas, in children prognosis rate is better as compared to adults.MATERIALS AND METHODS: Fifty (n=50) patients of leukemia and ﬁfty (n=50) were obtained and screened at Ganga Ram Hospital Lahore. Serum was separated and estimated for their 8hydroxy -2-deoxy guanosine, Isoprostanes, myeloperoxidase and cytokines such as TNF-α and several interleukins with their commercially available ELISA kits respectively. While neutrophils were estimated by the help of hematology analyzer and malondialdehyde (MDA) was estimatedby the method of Ohkawa.RESULTS: The results of the present study shows that variables of oxidative stressi.e., malondialdehyde (MDA), isoprostanes (IsoP-F2a), 8-hydroxy-2-deoxy guanosine (8-OHdG), neutrophils and cytokines including interleukin-6 (IL-6), tumor necrosis factor (TNF) and myeloperoxidase (MPO)diﬀered signiﬁcantly. The recorded levels of MDA (5.26±1.26 nmoles/ml), Isoprostanes (81.26±5.26 pg/ml), 8-OHdG (1.22±0.016 pg/ml), MPO (2.16±0.16 pg/ml) were signiﬁcantly increased as compared to controls. Levels of cytokines i.e., IL-6 and TNF-α remained (6.59±2.16pg/ml) and (56.26±2.26 pg/ml) in diseased group while in controls they were(0.965±0.16pg/ml) and (0.15±0.015pg/ml)respectively.CONCLUSION: Performed research work concludes that leukemic patients have positive relation among disease progression and oxidative stress. It is characterized by increased the levels of oxidative stress markers signiﬁcantly in serum concentration. Increased level of MDA signiﬁes increased lipid peroxidation in the subjects of leukemic patients.